1985
DOI: 10.2166/wst.1985.0235
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategies for Nutrient Removal Plant

Abstract: The first full-scale Bardenpho plant in the colder regions of North America was constructed in Kelowna and operated for about two years. The design was based on criteria developed by Barnard (1974) and based on experience of the design of similar plants in South Africa. Maximum flexibility leaving the operator many options for optimization was allowed. Effluent ortho-phosphate, nitrate and ammonia concentration averaged 0.43, 2.05 and 0.78 mg/ℓ respectively over the first year of operation. Operating results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Hence, an oxygen-free environment is required for a successful EBPR process (Barnard et al, 1985;Randall et al, 1998). Hence, an oxygen-free environment is required for a successful EBPR process (Barnard et al, 1985;Randall et al, 1998).…”
Section: Factors Affecting Ebprmentioning
confidence: 99%
“…Hence, an oxygen-free environment is required for a successful EBPR process (Barnard et al, 1985;Randall et al, 1998). Hence, an oxygen-free environment is required for a successful EBPR process (Barnard et al, 1985;Randall et al, 1998).…”
Section: Factors Affecting Ebprmentioning
confidence: 99%
“…Other areas of development may lie in plant production of easily degradable organics by fermentation of raw primary sludges (Barnard et al, 1985) and different combinations of biological and chemical phosphorus removal processes.…”
Section: Trends and Emerging Technologymentioning
confidence: 99%
“…The effects of temperature on the efficiency and the kinetics of excess biological phosphorus removal (EBPR) systems have been under investigation for the past two decades, but the studies have yielded contradictory results. Early researchers (Sell, 1981;Ekama, et al 1984; Barnard et al 1985) reported that EBPR efficiency was greater at lower temperatures than at higher temperatures over the range from 5 to 24 o C. The first contradictory finding was reported by McClintock et al (1992). They showed that EBPR functions would "wash-out" of activated sludge systems before other heterotrophic functions at a temperature of 10 o C and a sludge retention time (SRT) of 5 days, whereas wash-out did not occur at 10 o C when the SRT was 15 days.…”
Section: Introductionmentioning
confidence: 97%